Double Fuzzy $δ$-Continuous Functions in Double Fuzzy Topological Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce $(\mathfrak{r}, \mathfrak{s})$-$δ$-fuzzy closed sets in double fuzzy topological spaces and investigate some of their properties. Moreover, we introduce the concept of double fuzzy $δ$-continuous functions. Several interesting properties and characterizations are introduced and discussed. Furthermore, the relationships among the new concepts are introduced and established with some interesting counterexamples.
Keywords: Fuzzy sets, double fuzzy topological spaces, $(\mathfrak{r}, \mathfrak{s})$-fuzzy $δ$-closed sets, $(\mathfrak{r}, \mathfrak{s})$-fuzzy $δ$-continuous functions